Reconstruction of Dhaka City in the 18th Century by the Nawab Family in the Light of Islamic Civilization - Billah, Mutasim; Sadequzzaman, Md.; Kaosar, Md (CenRaPS Journal of Social Sciences, 2021)
The Khwaja family of Dhaka having obtained the title of 'Nawab' from the Government of British India reconstructed the city of Dhaka in the 18th century following the light of Islamic civilization. ‘Knowledge’ and ‘charity’ were the basic foundation of Islamic civilization. Similarly, In islamic civilization it was the regular activities to maintain sustainable public welfare oriented architecture. The contemporary period of the Nawab family, they made name and fame for themselves to perform their humanitarian activities. Through business income they developed a waqf system and spent it for various welfare purposes such as: patronage of modern education, institutions, medicine and technology; assistance to the people who were suffering in natural calamities in national and international arena, and they maintained friendship with government bureaucrats. In Islamic civilization we see various attributes such as: human rights, freedom of thought and practicing religion, Muslim family bondage, social welfare, medicine, orphanage, architecture, aesthetics of utensils, library, beauty of modern and scientific discoveries, beauty of environment, gardening, characteristic beauty, fine taste etc. In the eighteenth century, we found similar characteristics in Dhaka City which inspired us to compare the ‘Dhaka city’ reconstruction according to the light of ‘Islamic civilization’. If we see the nature of muslim’s city in medieavel period around the globe, then we found similar features. In this article we try to learn the hidden power of the Nawab family which led them to ‘reconstruct’ the `Dhaka city' through the exploration of various historical books, to see the current activities of their organization, trustees and observing their way of life.